Stendhal viajero: Memorias de un turista - Bravo Castillo, Juan (Revista de Filología Románica, 2006)
This article analyzes the route that Stendhal, following the great French Romantic authors, made through Italy - which he thought was his real homeland and where he began to write - and Europe. The works related to these journeys move away from the tourists’ guides clichés of that time, and express the need for a personal look on things and places, seeing unusual landscapes which can satisfy his spiritual wishes, or travelling just for professional reasons.